A NavPress Bible study on the book of 1 Peter (Colorado Springs, CO NavPress, 1986)
Includes bibliographical references.
Donated by Pieter Dijkstal, 5/2003.
Keywords: Bible. N.T. Peter, 1st -- study and teaching